Jogos locativos como mídia publicitária: um estudo de caso sobre o jogo ingress - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Technology is helping to constantly change the way consumption takes place in society. The aesthetic and performance aspects are reflected in the way companies relate to their audiences. The market is moving closer to entertainment and companies are trying to provide new experiences. In this way, this work has the general aim of understanding locative games as advertising vehicles, using the game Ingress and the brands with which it has interacted until the present moment. This research is a case study, for its realization it uses the techniques of bibliographic research and document analysis, from documents found in research, the game's official social network, community blogs and company websites. The theoretical implications encourage reflection on advertising acts and the use of games as an advertising medium.
Keywords: Jogos eletrônicos; Locação de serviços; Mídia social; Publicidade; Ingress; Video games; Service rental; CNPQ::CIENCIAS SOCIAIS APLICADAS